Simulation model for the natural progression of cervical cancer in Colombia (2016)
"The motivation for this research is the lack of real and representative data to estimate the probability of transitioning between the 6 true-health states of cervical cancer for Colombian women. Through the construction of a computational biology simulation model at the cellular level we reproduce the natural regression and progression of the CC disease and then compute the TPM. We aim to determine an estimate of the parameters that constitute the TPM, taking into account specific characteristics of the HPV infection and CC progression (e.g. incidence or prevalence) among Colombian woman".